2022
DOI: 10.3390/life12091400
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Baroreflex Sensitivity and Blood Pressure Variability Following Sport-Related Concussion

Abstract: Current methods to diagnose concussions are subjective and difficult to confirm. A variety of physiological biomarkers have been reported, but with conflicting results. This study assessed heart rate variability (HRV), spontaneous baroreflex sensitivity (BRS), and systolic blood pressure variability (BPV) in concussed athletes. The assessment consisted of a 5-min seated rest followed by a 5-min (0.1 Hz) controlled breathing protocol. Thirty participants completed baseline assessments. The protocol was repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Although this analysis focused on the longer-term effect of a history of concussion on autonomic nervous system functionality, there is stronger evidence to suggest that concussion has greater effects on the ANS in the more acute stages. Ellingson et al found SDNN to be depressed after a 5-min ECG recording in collegiate aged athletes 1–5 days post-concussion ( 42 ). Another study on Canadian hockey players found that while standing at rest, the concussed group had lower SDNN and nearly significant lowered RMSSD ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this analysis focused on the longer-term effect of a history of concussion on autonomic nervous system functionality, there is stronger evidence to suggest that concussion has greater effects on the ANS in the more acute stages. Ellingson et al found SDNN to be depressed after a 5-min ECG recording in collegiate aged athletes 1–5 days post-concussion ( 42 ). Another study on Canadian hockey players found that while standing at rest, the concussed group had lower SDNN and nearly significant lowered RMSSD ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this current study now highlight the importance of conducting baseline physiological testing at the beginning of a sporting season for any contact sport athletes. Recent research supports the use of baseline physiological testing for standardising pre-participation guidelines so that the medical staff responsible for getting players back-to-play safely, post-concussion, can provide an objective assessment of the players’ physiological status [ 5 , 41 ] to avoid early return-to-play and potential adverse complications.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research in the concussion literature that has examined the effects of sport-related concussion (SRC) on cerebral physiology has focused on the acute injury phase. This research has documented significant negative effects on brain and cardiac physiology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The acute physiological effects include altered cerebrovascular reactivity [ 10 , 14 , 15 ], cerebral oxygenation [ 16 ], baroreflex sensitivity [ 5 , 17 ], blood pressure variability [ 5 , 18 ], heart rate variability [ 3 , 19 , 20 , 21 ], dynamic cerebral autoregulation [ 22 , 23 , 24 ], and cardiac mechanics [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to blood pressure changes, the baroreflex shifts sympathetic tone through a negative feedback loop by adjusting HR. Baroreflex sensitivity (BRS) is the change in the interbeat interval when blood pressure changes [ 11 ] and is measured by regression of the R-R interval and systolic blood pressure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%